How social context impacts the emergence of leadership structures. (August 2022) - Roth, Philip
In leadership research, it has proven useful to understand leadership as a relational phenomenon and to conceptualize leadership structures as networks of leader-member ties. Currently, research further highlights the dynamic nature of these structures and examines their emergence in more detail to uncover the underlying mechanisms. In this literature, emergence is conceptualized as social exchange in teams and investigated experimentally. This paper argues that by doing so, the influence of social context has been neglected. I draw on findings from broader tie-formation research to substantiate the influence of social context and to tackle the conceptual shortcoming. Drawing on this rich literature, I identify eight mechanisms that explain in detail how four dimensions of social context ( Culture, Social Networks, Population Characteristics, and Opportunity Patterns ) shape the formation of leader-member ties. Finally, I derive 13 propositions based on these mechanisms. These propositions, on the one hand, provide solid starting points for further empirical research. On the other hand, they indicate that the underexposure of social context has led to an overly positive picture of emergent leadership in the current literature. They suggest that much more often than assumed so far, the wrong people become and remain leaders.